2020
DOI: 10.1002/dmrr.3399
|View full text |Cite
|
Sign up to set email alerts
|

Canola oil compared with sesame and sesame‐canola oil on glycaemic control and liver function in patients with type 2 diabetes: A three‐way randomized triple‐blind cross‐over trial

Abstract: Background This study aimed to compare the effects of sesame (SO), canola (CO), and sesame‐canola (SCO: a blend) oils on glycaemic control markers and liver function enzymes in adults with type 2 diabetes. Methods In this randomized, triple‐blind, three‐way, cross‐over clinical trial, participants replaced their usual oil with the intervention oils for 9 weeks. Serum fasting blood sugar, fasting serum insulin (FSI), insulin resistance (HOMA2‐IR), beta‐cell function (HOMA2‐%B), insulin sensitivity (HOMA2‐%S), q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 60 publications
0
43
0
Order By: Relevance
“…29 The results of our parent project 30 on other health-related aspects have been reported elsewhere. 29,[31][32][33] Because the metabolic responses to dietary interventions may differ between healthy individuals and those with chronic diseases, we examined the effects of dietary CO, SO and SCO on body weight and composition, which were assessed as secondary outcomes in a large controlled clinical trial conducted in patients with T2DM. In addition, although sex-specific effects are well acknowledged in some area of research, 34 they are not sufficiently elucidated in nutrition research studies.…”
Section: Introductionmentioning
confidence: 99%
“…29 The results of our parent project 30 on other health-related aspects have been reported elsewhere. 29,[31][32][33] Because the metabolic responses to dietary interventions may differ between healthy individuals and those with chronic diseases, we examined the effects of dietary CO, SO and SCO on body weight and composition, which were assessed as secondary outcomes in a large controlled clinical trial conducted in patients with T2DM. In addition, although sex-specific effects are well acknowledged in some area of research, 34 they are not sufficiently elucidated in nutrition research studies.…”
Section: Introductionmentioning
confidence: 99%
“…General characteristics of the included studies are reported in Table 1 . These studies were published between 2006 and 2020 and were conducted in Iran [ 14 , 25 , 26 , 28 ], India [ 16 , 27 ], Brazil [ 24 ], and Pakistan [ 15 ]. The age of the participants and the duration of intervention were 18–70 years and 6–12 weeks, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Only one article was conducted on women [ 24 ], and all other trials included males and females [ 14 16 , 25 – 28 ]. Sesame was evaluated as sesame oil [ 15 , 16 , 26 28 ], sesame seed [ 24 , 25 ], and sesamin supplement [ 14 ]. Six RCTs had a parallel design [ 14 16 , 24 , 25 , 28 ], while two studies had a crossover design [ 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The abundance of oleic acid in rapeseed oil may support its beneficial properties, as it has been shown that oleic acid elicits improvement on lipids and lipoproteins, as well as reduced risk of cardiovascular disease in humans [89]. The ALA content in rapeseed oil, in turn, is estimated at approximately 6 to 10% of total fatty acids [59,90,91]. Interestingly however, a study found a much lower ALA content in rapeseed oil, ≈1.2% [92].…”
Section: Rapeseed Oilmentioning
confidence: 99%
“…A critical interpretation of published studies will see that other plant sources of MUFAs and PUFAs may show positive results in comparison to rapeseed oil. For instance, the consumption of sesame oil was more favourable for glycaemic control markers when compared to rapeseed oil in a recent RCT recruiting individuals with type 2 diabetes mellitus [91]. In that study, rapeseed oil increased serum fasting blood glucose (+7.72 ± 3.15 mg/dL, p < 0.05), whilst sesame oil decreased serum insulin (−6.00 ± 1.72 mIU/mL, p < 0.05) levels in a nine-week intervention period.…”
Section: Rapeseed Oilmentioning
confidence: 99%